Evaluating Digital Governance Strategy Through SWOT–IFAS–EFAS Analysis A Case Study Of Srikandi Implementation In The East Kalimantan Provincial Government - Rosyid Nurrohman; Ryan Muhyiddin Anwar Ryan (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study aims to evaluate digital governance strategies through SWOT, IFAS, and EFAS analyses of the implementation of the SRIKANDI application within the East Kalimantan Provincial Government. SRIKANDI, a digital archiving system developed by the National Archives of the Republic of Indonesia, plays a role in improving the efficiency, transparency, and accountability of government administration. The research method used a qualitative descriptive approach to identify internal and external factors influencing system implementation. The analysis results indicate that key strengths lie in regulatory support, increased work efficiency, and archive digitization, while weaknesses include limited human resource competency and technical constraints. Opportunities include support for government digital transformation policies, while threats relate to infrastructure readiness and resistance to change. Overall, SRIKANDI implementation is strategically positioned to support the sustainable strengthening of digital governance.